The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica - Longino, John T. (Zootaxa, 2003)
The taxonomy and natural history of the ant genus Crematogaster are reviewed for the Costa Rican fauna. Thirtyone species are known, and a key is provided for these and two additional species from adjacent regions of Panama. Species boundaries are evaluated over their entire range when possible. The taxonomic history of the genus is one of unbridled naming of new species and subspecies, with no synthetic works or keys. Major taxonomic changes are proposed, with the recognition of several polytypic species with very broad ranges and the synonymization of the many names associated with them. Crematogaster pygmaea Forel 1904, suturalis Forel 1912, ornatipilis Wheeler 1918, erici Santschi 1929, and chacoana Santschi 1933 are synonymized under abstinens Forel 1899; centralis Santschi 1932 under acuta (Fabricius 1804); aruga Forel 1913 under arcuata Forel 1899; ludio Forel 1912, armandi Forel 1921, inca Wheeler 1925, and cocciphila Borgmeier 1934 under brasiliensis Mayr 1878; parabiotica Forel 1904 under carinata Mayr 1862; brevispinosa Mayr 1870, minutior Forel 1893, schuppi Forel 1901, recurvispina Forel 1912, sampaioi Forel 1912, striatinota Forel 1912, townsendi Wheeler 1925, and chathamensis Wheeler 1933 under crinosa Mayr 1862; barbouri Weber 1934 under cubaensis Mann 1920; antillana Forel 1893, sculpturata Pergande 1896, kemali Santschi 1923, accola Wheeler 1934, phytoeca Wheeler 1934, panamana Wheeler 1942, and obscura Santschi 1929 under curvispinosa Mayr 1870; descolei Kusnezov 1949 under distans Mayr 1870; projecta Santschi 1925 under erecta Mayr 1866; carbonescens Forel 1913 under evallans Forel 1907; palans Forel 1912, ascendens Wheeler 1925, and dextella Santschi 1929 under limata F. Smith 1858; agnita Wheeler 1934 under obscurata Emery 1895; amazonensis Forel 1905, autruni Mann 1916, and guianensis Crawley 1916 under stollii Forel 1885; surdior Forel 1885, atitlanica Wheeler 1936, and maya Wheeler 1936 under sumichrasti Mayr 1870; tumulifera Forel 1899 and arizonensis Wheeler 1908 under torosa Mayr 1870. The following taxa are raised to species: ampla Forel 1912, brevidentata Forel 1912, chodati Forel 1921, crucis Forel 1912, cubaensis Mann 1920, goeldii Forel 1903, malevolens Santschi 1919, mancocapaci Santschi 1911, moelleri Forel 1912, montana Borgmeier 1939, obscurata Emery 1895, rochai Forel 1903, russata Wheeler 1925, sericea Forel 1912, stigmatica Forel 1911, sub-tonsa Santschi 1925, tenuicula Forel 1904, thalia Forel 1911, uruguayensis Santschi 1912, and vicina Andre 1893. The following new species are described: bryophilia, flavomicrops, flavosensitiva, foliocrypta, jardinero, levior, monteverdensis, raptor, snellingi, sotobosque, and wardi.